Infection Rate in Cholecystectomy using Cidex Sterilized Versus Autoclaved Sterilized Instruments - Muhammad Azhar, Sadia, Syed Arif Hussain, Kumail Haider, Malaka Fatima, Ayesha Farooq (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Cholecystectomy is a common procedure for removal of the gall bladder which is preferred to be conducted laparoscopically. The infection of cholecystectomy varies on several factors. one important factor is sterilization of laparoscopic ports and instruments. By opting for a better sterilization method of the instrument, the surgical site infections can be prevented up to a great extent. Objective: To determine and compare the rate of infection through cidex sterilized versus autoclave sterilized instruments in patients undergoing laparoscopic cholecystectomy Study design: Comparative analytical study Place and duration of study: Department of Surgery, Muhammad Aslam Chaudary Hospital, Wah Cantt from 1st March 2023 to 31st August 2023. Methodology: One hundred and five patient undergoing cholecystectomy were enrolled in the study between the age 10-55 years. These patients were randomly divided into two groups as Group A (n=55) and Group B (n=50) through double blinding mechanism. The groups were assigned according to the opted sterilization procedure for the instruments. In group A cases the instruments were sterilized by Cidex while in group B autoclaving sterilization was applied. All the relevant clinical data and study findings were entered in a well structured questionnaire. The data was analyzed and compared within groups and results were interpreted. Result: The mean age group was 42.3±3.5 years and 47.2 ±2.5 years in Group A and Group B respectively. Majority of the patients had surgery duration of 51-60 minutes followed by 41-50 minutes. There was an overall increase in infection cases with the increasing time of surgery however there was significantly higher number of port site infections in Group A (14.5%) them Group B (2%). A total of 8.5% of the cases who underwent laparoscopic cholecystectomy developed port site infections. Conclusion: The autoclave sterilization method is a better option of instrument sterilization than CIDAX sterilization technique. Keywords: Infection, Cholecystectomy, Cidexsterilized, Instrument